(untitled) (Journal of Medical & Health Sciences Review, 2025)
Aim: In current study, volatile organic compounds released from yeast Kluyveromyces marxianus were investigated for their inhibitory activity against plant-pathogenic fungi Aspergillus niger. Methods and Results: A screening revealed that volatile organic compounds from yeast K. marxianus AHT-4 remarkably inhibited the colony formation of plant-pathogenic fungi while also inhibiting the conidial germination of phytopathogenic Aspergillus niger. The volatile organic compounds were isolated from the culture filtrate of K. marxianus and different alkanes were identified as major compounds. Conclusions: A mixer of isolated alkanes, nonadecanes, eicosane, docosane and tetracosane, was used to determine the antifungal activties. Significance and Impact of the Study: This study provides significance antimicrobial activity of yeast volatile compounds which have novel biological control for inhibiting various fruit and vegetable rotting fungal diseases. It’s provided a best alternate way to overcome the disadvantages associated with chemical fungicides used against phyto-pathogenic fungi.